Development of a universal first aid kit: current trends and approaches to training - A. I. Lemeschewskij; S. S. Lemiasheuskaya; A. Yu. Pochtavtsev; V. A. Hiniuk; О. B. Pavlov (Military Medicine, 2026)
First aid training of medical students in an international educational environment is associated with certain risks arising from the lack of unified requirements for the composition of universal first aid kits. Objective. T o analyse national characteristics in the development of universal first aid kits and to identify methodological approaches for training international medical students, taking into account the 2025 European and American first aid guidelines. Materials and methods. A comparative analysis was conducted of regulatory documents governing the composition of universal first aid kits: the Republic of Belarus (Resolution of the Ministry of Health of the Republic of Belarus No. 178 of 23 November 2023, with amendments in 2024), the European Union (DIN 13157:2022), and the United States (ANSI/ISEA Z308.1-2021). The composition, structure, and mandatory components of first aid kits were assessed, and key trends were identified. Results. Significant differences in approaches to first aid kit development were identified. In the Republic of Belarus, a medication-based model predominates, including medicinal products and medical devices; in Europe and the United States, a non-medication-based model prevails, with an emphasis on dressings. Conclusions . Pronounced national differences exist in the composition of universal first aid kits, while unified criteria for assessing the effectiveness of different approaches are currently lacking. These differences should betaken into account when developing educational programmes for international medical students, particularly with regard to the safe and rational use of medicinal products. Adherence to international first aid guidelines may reduce the risk of errors when providing first aid under differing national standards.